(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
the article examines the impact of legal certainty in commodity classification and the institution of advance rulings issued by customs authorities on the economic effectiveness of foreign economic activity. The author considers classification not merely as a legal and technical procedure for assigning goods to codes of the Commodity Nomenclature of Foreign Economic Activity (CN FEA), but also as an instrument for managing fiscal risks, time losses, logistical delays, and compliance costs borne by participants in foreign trade. On the basis of materials relating to Uzbekistan, the provisions of the Harmonized System, the rules of the Customs Code of the Republic of Uzbekistan, and contemporary international approaches, the article proposes a model in which an advance classification ruling and digital verification of commodity characteristics serve as key factors in reducing transaction costs and increasing the predictability of customs administration.